Exploring the effects of Metta meditation on emotional regulation: using semi structured interviews on adult novice meditators - Daly, Alexander (The IIE, 2020)
The inability to effectively regulate one’s emotions is linked to a variety of maladaptive behaviours and cognitive processes such as, psychotic symptoms, childhood trauma and negative affect (Bradley, DeFife, Fani, Guarnaccia, Phifer, Ressler & Westen, 2015). A global increase in anxiety and depression over the past several years (World Health Organization, 2017) calls for research into emotional stability and emotional regulation, and possible strategies to increase well-being. the study aimed to explore the effects of Metta mediation on emotional regulation, as well as other possible benefits of Metta mediation on emotions and well-being. The study was conducted on five novice Metta meditators that were recruited using purposive sampling. The study was qualitative. The data was collected using semi-structured interviews, as flexibility in the data collection process is important for an explorative qualitative study. The data was analyzed using thematic analysis. the study did not find a direct link between Metta mediation and emotional regulation. However, the participants reported experiencing increased compassion, benevolence, awareness, intent, and overall positive affect in relation to their Metta mediation practice. Further research needs to be conducted to determine whether Metta meditation is an effect strategy that can be used to increase individual's positive emotions and well-being.
Keywords: Metta meditation; Emotional regulation; Adults; Novice meditators